2005
DOI: 10.1080/14786410412331280041
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bryostatins and potential precursors from the bryozoan Bugula neritina

Abstract: The bryozoan species Bugula neritina contains the anticancer agent bryostatin. Bryostatin has been extracted from these sessile marine invertebrates since the late 1960s from the Gulf of California, Gulf of Mexico, as well as various locations on the eastern and western rims of the Pacific Ocean. In this work we are focusing on animals harvested in the Gulf of Mexico near Alligator Point (Florida). Using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) we measure the concentration of 70 elements in B. ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Bryostatin has been extracted from bryozoan Bugula neritina since the late 1960s mainly from the area of the Gulf of California, Gulf of Mexico and from various locations on the eastern and western rims of the Pacific Ocean including Japan (Ueno et al, 2012). The extract analyses of 14 various marine animal species of the Gulf of Mexico have, among others, proved the occurrence of substances with bryostatin structure in other marine organisms of various taxonomy submission, which suggests that bryozoans may not necessarily be the one and only original source of bryostatins (Manning et al, 2005).…”
Section: Sources Of Bryostatinmentioning
confidence: 99%
“…Bryostatin has been extracted from bryozoan Bugula neritina since the late 1960s mainly from the area of the Gulf of California, Gulf of Mexico and from various locations on the eastern and western rims of the Pacific Ocean including Japan (Ueno et al, 2012). The extract analyses of 14 various marine animal species of the Gulf of Mexico have, among others, proved the occurrence of substances with bryostatin structure in other marine organisms of various taxonomy submission, which suggests that bryozoans may not necessarily be the one and only original source of bryostatins (Manning et al, 2005).…”
Section: Sources Of Bryostatinmentioning
confidence: 99%
“…The bryozoan Bugula neritina Linnaeus, 1758, attracts significant interest as an important source of the cytotoxic chemicals bryostatins (Davidson et al 2001;Lopanik et al 2004;Manning et al 2005;Sharp et al 2007;Lei et al 2010), which are potential anti-cancer agents now under clinical investigation. Previous studies of the mitochondrial gene cox1 have suggested that B. neritina is a complex of three cryptic species, namely Types S (shallow), D (deep) and N (North Atlantic) (McGovern and Hellberg 2003;Mackie et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Particularly, electrospray ionization Fourier transform ion cyclotron resonance multiple-stage tandem mass spectrometry (ESI-FT-ICR-MS n ) is very useful for the structural confirmation of natural products due to the ability of providing precise elemental compositions [16][17][18] and its SORI (Sustained Off Resonance Irradiation) technique which can provide abundant fragment ions information of target precursor ions. And high performance liquid chromatography-electrospray ionization multiple-stage tandem mass spectrometry (HPLC-ESI-MS n ) has been used more frequently in the analysis of active components of natural products recently.…”
Section: Introductionmentioning
confidence: 99%